Radiation-Induced Papillary Meningioma: A Case Report - Manivel, Manoj Kumar; Vivek, Visweswaran; Ganesh, Krishnamurthy (Asian Journal of Neurosurgery, 2022)
Meningiomas are the most common tumors that develop following cranial radiotherapy. They have a shorter latency period and an aggressive behavior when compared with spontaneously occurring meningiomas. We report a 69-year-old male who underwent high-dose radiotherapy for recurrent pituitary adenoma and later developed temporal high-grade meningioma which was excised. Patient developed tumor bed bleed twice in the postoperative period and succumbed subsequently to the disease. After a thorough review of literature, this may be the second case of radiation-induced grade III papillary meningioma which has been reported.
Keywords: radiation-induced meningioma; spontaneous meningioma; pituitary adenoma; fungal sinusitis